Getting Your Point Across - Phillip Khan-Panni (Macmillan Publishers India, 2007)
Have you ever made a presentation and noticed that some in your audience were not listening? Ever had a conversation with a person who kept looking over your shoulder for someone more interesting? Ever tried to make your point in a meeting, only for the chair to cut you off before you had finished? If anything like that has ever happened to you, you need this book. Getting your point across quickly and effectively is a skill that will get you noticed and give you the competitive edge in business. It will make you more interesting, give you the high ground in group discussions, gain you the respect and even the admiration of your peers.